The Relationship Between Leadership Style and Organizational Entrepreneurship in the Staff Managers of Ahvaz Jundishapur University of Medical Sciences - Nayeb Fadaei Dehcheshmeh (Shahid Sadoughi University of Medical Sciences, 2023)
Nayeb Fadaei Dehcheshmeh 3* 3 Department of Public Health, Shoushtar Faculty of Medical Sciences, Shoushtar, Iran Corrigendum notice: In the above article, which was published in the Volume 6, Issue of 2, June 2022, affiliation of Nayeb Fadaei Dehcheshmeh has been corrected.